2018
DOI: 10.3390/microorganisms6030057
|View full text |Cite
|
Sign up to set email alerts
|

PBP4: A New Perspective on Staphylococcus aureus β-Lactam Resistance

Abstract: β-lactam antibiotics are excellent drugs for treatment of staphylococcal infections, due to their superior efficacy and safety compared to other drugs. Effectiveness of β-lactams is severely compromised due to resistance, which is widespread among clinical strains of Staphylococcus aureus. β-lactams inhibit bacterial cells by binding to penicillin binding proteins (PBPs), which perform the penultimate steps of bacterial cell wall synthesis. Among PBPs of S. aureus, PBP2a has received the most attention for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 44 publications
1
25
1
5
Order By: Relevance
“…Interestingly, inhibition of PBP4 activity has been shown to diminish cell wall cross-linking in β-lactam heteroresistant MRSA strains but had no effect on cross-linking in homoresistant strains (48). Currently, little is known about the regulation of PBP4 expression (49); however, further investigations into the effect of NaHCO 3 on PBP4 protein production may offer additional insights into mechanisms underlying NaHCO 3 -responsive versus NaHCO 3 -nonresponsive phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, inhibition of PBP4 activity has been shown to diminish cell wall cross-linking in β-lactam heteroresistant MRSA strains but had no effect on cross-linking in homoresistant strains (48). Currently, little is known about the regulation of PBP4 expression (49); however, further investigations into the effect of NaHCO 3 on PBP4 protein production may offer additional insights into mechanisms underlying NaHCO 3 -responsive versus NaHCO 3 -nonresponsive phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that pbp4 expression is tightly controlled, as it is dynamically tuned in response to local antibiotic concentrations [49]. Recently, studies have shown that PBP4 may play an important role in S. aureus resistance to β-lactam antibiotics [40,[50][51][52][53]. Therefore, other factors contributing to the regulation of pbp4 activity should be investigated further, including wall teichoic acids, shown to act as spatial and temporal regulations of PBP4 mediated peptidoglycan crosslinking [54], and PBP2, which has been shown to interact with PBP4 during cell wall synthesis [55].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Interestingly, inhibition of PBP4 activity has been shown to diminish cell wall cross-linking in β-lactam hetero-resistant MRSA strains, but had no effect on cross-linking in homo-resistant strains (48). Currently, little is known about the regulation of PBP4 expression (49); however, further investigations into the effect of NaHCO 3 on PBP4 protein production may offer additional insights into mechanisms underlying NaHCO 3 -responsive vs NaHCO 3 -nonresponsive phenotypes.…”
Section: Discussionmentioning
confidence: 99%